Sport tourism development - Higham James; Hinch Thomas (New Delhi Viva Books, 2006)
Sport and tourism are global social and economic phenomena that increasingly demonstrate a convergence of business, planning and management interests. In setting the foundation for this book, the unique qualities of sport as a tourist attraction are pres
Keywords: Sport tourism; Tourism